Pengaruh Disiplin dan Kepatuhan Kerja Terhadap Kinerja Pegawai PT. Marugo Rubber Indonesia Cabang Karawang - Dandi Rizaldi; Enjang Suherman; Laras Ratu Khalida (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Implementing good work discipline and compliance with Work Instructions (WI) is very necessary in order to avoid or reduce the risk of Not Good (NG) goods. The aim of the research is to determine the relationship between discipline and work compliance on the performance of PT employees. Marugo Rubber Indonesia Karawang branch. Using quantitative research methods, the sample for this research is employees of PT. Marugo Rubber Indonesia Karawang branch has 175 employees. Management of the data available in this research uses calculations with the help of the Statistical Product and Service Solution (SPSS) version 27 program. The results in this research are that most employees are disciplined and obedient in carrying out work processes according to Work Instructions (WI), namely 43.3%. The results of the hypothesis test in this study produced 0.001 < 0.05, so partially there is quite a significant relationship between work discipline (X1) and work compliance (X2) on employee performance (Y).